Oriental schistosomiasis with neurological complications: case report - Li, Yuesheng (BioMed Central, 2011)
We describe a case of cerebral schistosomiasis, caused by Asian (oriental) Schistosoma japonicum trematode blood flukes, in a young Chinese patient and its management. We also provide a brief update for physicians on the clinical features, diagnosis and treatment of schistosomiasis, with particular emphasis on neuroschistosomiasis, the most severe clinical outcome associated with this parasitic infection.